2023
DOI: 10.3389/fonc.2023.1134763
|View full text |Cite
|
Sign up to set email alerts
|

GD2 and GD3 gangliosides as diagnostic biomarkers for all stages and subtypes of epithelial ovarian cancer

Abstract: BackgroundOvarian cancer (OC) is the deadliest gynecological cancer, often diagnosed at advanced stages. A fast and accurate diagnostic method for early-stage OC is needed. The tumor marker gangliosides, GD2 and GD3, exhibit properties that make them ideal potential diagnostic biomarkers, but they have never before been quantified in OC. We investigated the diagnostic utility of GD2 and GD3 for diagnosis of all subtypes and stages of OC.MethodsThis retrospective study evaluated GD2 and GD3 expression in bioban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Previous studies have indicated increased gangliosides levels in OC cell lines, tissues, serum, as well as ascites fluid from OC patients 23, 24 , suggesting gangliosides could play a role as OC markers. However, existing data is still sparse regarding the importance of these glycolipids in OC development 23 . A total of twenty-two ganglioside species were detected in serum by LC-MS ( Table S5 ), and their structures confirmed by tandem MS experiments.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Previous studies have indicated increased gangliosides levels in OC cell lines, tissues, serum, as well as ascites fluid from OC patients 23, 24 , suggesting gangliosides could play a role as OC markers. However, existing data is still sparse regarding the importance of these glycolipids in OC development 23 . A total of twenty-two ganglioside species were detected in serum by LC-MS ( Table S5 ), and their structures confirmed by tandem MS experiments.…”
Section: Resultsmentioning
confidence: 92%
“…The heterogeneity of OC is one major obstacle in biomarker discovery 23 . HGSC accounts for only 30% of early-stage OC, but 86% of advanced-stage OC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations